An experimental and theoretical investigation of XPS and NEXAFS of 5-halouracils. Issue 9 (19th February 2018) - Castrovilli, M. C.; Bolognesi, P.; Bodo, E.; Mattioli, G.; Cartoni, A.; Avaldi, L.
Abstract : Experimental and DFT-based theoretical studies of XPS and NEXAFS of 5-halouracils reveal the aromatic/conjugate properties of these molecules. Abstract : The C, N and O 1s excitation and ionization processes of 5X-uracil (X = F, Cl, Br, and I) were investigated using near edge X-ray absorption fine structure (NEXAFS) and X-ray photoemission (XPS) spectroscopies. This study aims at the fine assessment of the effects of the functionalization of uracil molecules by halogen atoms having different electronegativity and bound to the same molecular site. Two DFT-based approaches, which rely on different paradigms, have been used to simulate the experimental spectra and to assign the corresponding features. The analysis of the screening of the core holes of the different atoms via electronic charge density plots has turned out to be a useful tool to illustrate the competition between the partially aromatic and partially conjugate properties of this class of molecules.